Experimental and Numerical Investigation of the Water-Exit Behaviour of an Inverted T-Shaped Beam - Xueyi Li; Feidong Zheng (Advances in Civil Engineering)
Water-exit is a hydraulic phenomenon induced when an object exists in a body of water. In the case of ship lifts, the hydrodynamic forces induced by the water-exit of the chamber’s support beam may result in unsafe and unstable operating conditions and may even cause a loss of structural integrity. In this study, the water-exit process of a simplified beam was investigated using an experimental–numerical approach. The experimental results revealed that three major stages occur during water-exit: start-up, flow-around, and exit-moment. Moreover, the maximum additional hydrodynamic load exerted on the beam during water-exit occurred in the exit-moment phase. Based on these results, a calibrated numerical method was employed to analyse the main factors affecting the maximum additional hydrodynamic load. The numerical results indicated that the additional load can be accurately predicted using two dimensionless parameters. These results may help evaluate the negative impacts of suction on a ship lift chamber and improve the technical support and operation of ship lifts.